Functional properties of amaranth, quinoa and chia proteins and the biological activities of their hydrolyzates - López, Débora Natalia (2018)
Fil: López, Débora. Pontificia Universidad Católica Argentina. Facultad de Química e Ingeniería del Rosario; Argentina